Influence of stunning methods on the welfare of glycerine-fed lambs - Santos, Viviane Correa [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; De Oliveira D'Aurea, Elisa Marcela [UNESP]; Fávaro, Vanessa Ruiz [UNESP]; Da Silva, David Attuy Vey [UNESP]; Júnior, Antonio Carlos Homem [UNESP]; Lage, Josiane Fonseca [UNESP]; Negrão, João Alberto (Universidade Estadual de Londrina, 2014)
The effects of electrical and non-penetrating bolt pistol stunning methods were evaluated. Forty uncastrated, mixed-breed (1/2Santa Inês × 1/2Dorper) males were used. The welfare of lambs was not affected (P> 0.05) by the inclusion of glycerin in the diet. The color of the meat (24 hours after slaughter) of lambs stunned with a non-penetrating bolt pistol was lighter (P> 0.05). The shear force, water-holding capacity, lipid oxidation and sarcomere length were not influenced by diet and stunning methods and exhibited average values of 1.59 kgf/cm2, 59.65%, 0.62 mg/kg and 2.26 μ, respectively. The animals stunned by electrical stimulation had a higher concentration of total leukocytes (7.22 × 103/μL) and creatine kinase (81.89 U/L). Based on welfare and meat quality, the non-penetrating bolt pistol can be considered an alternative stunning method for lambs.
Keywords: Blood parameters; Electrical stimulation; Meat quality; Non-penetrating bolt pistol; Sheep